2012
DOI: 10.1016/j.cell.2011.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Tension Maintains Cell Polarity by Confining Signals to the Leading Edge during Neutrophil Migration

Abstract: SUMMARY Little is known about how neutrophils and other cells establish a single zone of actin assembly during migration. A widespread assumption is that the leading edge prevents formation of additional fronts by generating long-range diffusible inhibitors or by sequestering essential polarity components. We use morphological perturbations, cell severing experiments, and computational simulations to show that diffusion-based mechanisms are not sufficient for long-range inhibition by the pseudopod. Instead, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
575
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 525 publications
(630 citation statements)
references
References 61 publications
35
575
3
Order By: Relevance
“…It has been shown that increasing membrane tension results in numerous intracellular signaling events, including the inhibition of Rac activation and actin assembly (20,39). Our results agree with these findings.…”
Section: Membrane Tension As a Signal For Late-stage Phagocytosissupporting
confidence: 93%
See 3 more Smart Citations
“…It has been shown that increasing membrane tension results in numerous intracellular signaling events, including the inhibition of Rac activation and actin assembly (20,39). Our results agree with these findings.…”
Section: Membrane Tension As a Signal For Late-stage Phagocytosissupporting
confidence: 93%
“…When we compare the FP spreading dynamics with measurements of cortical tension behavior during traditional phagocytosis reported by Lam et al (17,18) and Herant et al (19), we find that the onset of contraction coincides with points at which tension is likely to increase. This agrees with the finding that frustrated phagocytic spreading by RAW264.7 macrophages slows/halts due to an increase in membrane tension and that tension appears to regulate the actin-machinery-related signal Rac1 (20,21). To further investigate the link between tension and contraction, we subjected the cells to hyperosmotic shock to decrease the membrane cortical tension.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Since alterations in adhesion forces, cell spreading and membrane tension have been reported as being responsible for defective cell migration [23][24][25][26], we tested the ability of Myo1g-deficient B cells to migrate toward a chemokine gradient. We used CXCL13 to induce migration of resting B lymphocytes over a fibronectincoated surface in a chemotaxis chamber.…”
Section: Slow B-cell Migration In Vitro and Defective Homing In Vivomentioning
confidence: 99%